PENGARUH PELAYANAN PEMBIAYAAN DALAM MENINGKATKAN PEMASARAN KPR BERSUBSIDI DI KECAMATAN PASIR NANGKA TIGARAKSA PROPINSI BANTEN - Nurhadi, - (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2016)
The population at 30 people, especially consumers Tangerang regency research data were collected using a questionnaire and analyzed by SPSS. The results of the study calculations, the number of correlation between the effect of financing services to improve the marketing of mortgages in the district of Pasir Nangka Tigaraksa Banten province by cost 0415, a correlation of 0415 means that there is the influence of services between financing in improving the marketing of mortgages in the district of pasir nangka  Tigaraksa province of Banten quite strong and unidirectional (for the result is positive), the direction means that if the service is high, the savings and credit cooperatives in improving the marketing of mortgage loans is also high. The correlation between the two variables are significant because significant numbers of 0.000 <0.05. The magnitude of the numbers R Square (r2) by 0172 that number could be used to see the effect of financing services to improve the marketing of mortgages in the district of Pasir Nangka Tigaraksa (determinant coefficient). These figures are intentions that influence financing services to improve the marketing of mortgage credit in the district of pasir nangka  Tigaraksa cost is 72% and the rest influenced by other variables of 0.28%. Hypothesis test results F count = 2,804, compared with F table that uses the 5% error level  value F table = 2.36 so F count> F table (2.804> 2:36), then Ho is rejected and Ha accepted, meaning there is influence finance services to enhance the marketing of mortgages in the district of Pasir Nangka Tigaraksa Banten Province Keywords: services, credit financing, marketing